MEMAHAMI TERMINOLOGI SAMARIA DAN ORANG ASING DALAM LUK. 17:11-19 - Harmansi, Stanislaus Efodius (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2023)
Luke 17,11-19 is one of the episodes about the Samaritan in the Gospel of Luke. In this episode, the existence of verses 16b-18 is very interesting. In terms of plot, their presence can be eliminated. Without them, the plot remains coherent and even all its stages are fulfilled. The aim of this study is to describe their function in the stories about the Samaritan in the Gospel of Luke. In terms of function, their presence is very important. The significance of these verses is contained in the two ethnic identities, namely the Samaritan and the foreigner, which are used for the man who returns to Jesus after his healing. These two identities were mentioned when Jesus compared him to others who did not appear before him even though they had been healed. The use of these terms in this comparative framework, on the one hand wants to express Jesus' positive perception of the Samaritans and on the other hand depicts his criticism of the negative perspective of the Jews regarding the Samaritans.